Cardiac Sympathetic Denervation Suppresses Atrial Fibrillation and Blood Pressure in a Chronic Intermittent Hypoxia Rat Model of Obstructive Sleep Apnea. Issue 4 (19th February 2019) - Yang, Xuechao; Zhang, Linfei; Liu, Huan; Shao, Yongfeng; Zhang, Shijiang
Abstract : Background: Chronic intermittent hypoxia (CIH) is a distinct pathological mechanism of obstructive sleep apnea (OSA), which is recognized as an independent risk factor for cardiovascular diseases. The aims of this study were to ascertain whether CIH induces atrial fibrillation (AF), to determine whether cardiac sympathetic denervation (CSD) can prevent it and suppress blood pressure, and to explore the potential molecular mechanisms involved. Methods and Results: Sixty Sprague‐Dawley male rats were randomly divided into 4 groups: sham, CSD, CIH, CIH+CSD. The rats were exposed either to CIH 8 hours daily or normoxia for 6 weeks. Cardiac pathology and structure were analyzed by hematoxylin and eosin staining and echocardiogram. ECG, blood pressure, body weight, and blood gas were recorded. Connexin 43 and tyrosine hydroxylase were detected by western blot, immunohistochemistry, and immunofluorescence. CIH induced atrial remodeling, and increased AF inducibility. CSD treatment reduced postapneic blood pressure rises and AF susceptibility, which could attenuate CIH‐associated structural atrial arrhythmogenic remodeling. In addition, CIH‐induced sympathetic nerve hyperinnervation and CSD treatment reduced sympathetic innervation, which may affect CIH‐induced AF‐associated sympathovagal imbalance. Connexin 43 was specifically downregulated in CIH, whereas CSD treatment increased its expression. Conclusions: These results suggested CIH induces atrial remodeling, increases AF inducibility, results in sympathetic nerve hyperinnervation, and decreases connexin 43 expression, but CSD treatment reduces AF susceptibility, postapneic blood pressure increase, sympathetic innervation, and the alteration of Cx43, which may be a key point in the genesis of CIH‐induced AF.